THE ROLE OF THE FAMILY IN THE UPBRINGING OF PRESCHOOL CHILDREN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes the role of family life for a person, the upbringing of a harmonious personality in a family, parental responsibilities, parental authority, parental example, upbringing based on family traditions, profession, moral and spiritual values, the formation of a feeling of mutual affection, respect, preparation for family life.